Frontiers of Additively Manufactured Metallic Materials - Amir A. Zadpoor (Materials, 2018)
Additive manufacturing (AM) (=3D printing) has emerged during the last few years as a powerful technological platform for fabrication of functional parts with unique complex geometries and superior functionalities that are next to impossible to achieve using conventional manufacturing techniques. Due to their importance in industrial applications and the maturity of the applicable AM techniques, metallic materials are at the forefront of the developments in AM. In this editorial, which has been written as a preamble to the special issue “Perspectives on Additively Manufactured Metallic Materials”, I will highlight some of the frontiers of research on AM of metallic materials to help readers better understand the cutting edge of research in this area. Some of these topics are addressed in the articles appearing in this special issue, while others constitute worthy avenues for future research.